Meta-Analysis of Antidepressant Pharmacotherapy in Patients Eligible for Cardiac Rehabilitation: ANTIDEPRESSANT AMBIVALENCE. Issue 6 (30th November 2022) - Hughes, Joel W.; Kuhn, Tyler A.; Ede, David; Gathright, Emily C.; Josephson, Richard A.
Abstract : The efficacy of antidepressants for depression in patients eligible for cardiac rehabilitation was evaluated in a meta-analysis of 12 trials comparing antidepressants with placebo. The effect of antidepressants was small, and smaller among patients with heart failure. No safety concerns were noted. No trials evaluated antidepressants concurrent with cardiac rehabilitation participation. Abstract : Purpose: Many patients exhibit clinically significant depression upon enrollment in cardiac rehabilitation (CR). Antidepressants are a first-line treatment option for depression, but the effectiveness of antidepressants in patients with heart disease is mixed. The purpose of this meta-analysis was to evaluate the efficacy of antidepressants for depression in patients eligible for CR. Methods: A meta-analysis was conducted including randomized controlled trials of antidepressants from January 1990 to September 2021 that compared antidepressants with placebo. Random-effects models were used between group effect sizes (Hedges' g ). Results: A total of 13 trials with predominately White (68% ± 12; n =7) male (70% ± 11) samples averaging 61 ± 5 yr compared antidepressants (1128 participants) with placebo (1079 participants). Antidepressants reduced depressive symptoms ( g = 0.17: 95% CI, 0.08-0.27), but the effect was small. Heterogeneity among study effects was low ( I 2 = 6.42) and nonsignificant ( Q = 10.75, P = .46), although patients with heart failure ( g HF = 0.05: 95% CI, −0.09 to 0.18) demonstrated smaller effects compared with patients with other cardiovascular disease conditions (gnon-HF = 0.22: 95% CI, 0.11-0.32) ( Q B [1] = 3.97; P < .05). No study reported safety concerns associated with antidepressants. Summary: The effect size of antidepressant pharmacotherapy in this population is small. No trials reported on the combined effects of exercise and pharmacotherapy. If the patient is not suicidal, CR staff may consider patient preference and refer patients for additional treatment as necessary.